Child Labor, Schooling, and Child Ability - Akresh, Richard; Bagby, Emilie; de Walque, Damien; Kazianga, Harounan (2012)
Using data collected in rural Burkina Faso, this paper examines how children's cognitive abilities influence households' decisions to invest in their education. To address the endogeneity of child ability measures, the analysis uses rainfall shocks experienced in utero or early childhood to instrument for ability. Negative shocks in utero lead to 0.24 standard deviations lower ability z-scores, corresponding with a 38 percent enrollment drop and a 49 percent increase in child labor hours compared with their siblings. Negative education impacts are largest for in utero shocks, diminished for shocks before age two, and have no impact for shocks after age two. The paper links the fetal origins hypothesis and sibling rivalry literatures by showing that shocks experienced in utero not only have direct negative impacts on the child's cognitive ability (fetal origins hypothesis), but also negatively impact the child through the effects on sibling rivalry resulting from the cognitive differences.